Translation, cross-cultural adaptation and validation of the 10-item Weekly Calendar Planning Activity in Spanish-speaking ABI patients: a multicenter study - Salazar-Frías, Daniel; Funes, María Jesús; Merchán-Baeza, Jose Antonio; Ricchetti, Giorgia; Torralba-Muñoz, Jose Maria; Rodríguez-Bailón, María (Frontiers in Psychology, 2023)
We present the process of translation, adaptation, and validation in the Spanish context of the 10-item version of the Weekly Calendar Planning Activity (WCPA-10), a performance-based measure of cognitive instrumental activities of daily living (C-IADL). The study consisted of two phases: I) translation/cultural adaptation of the WCPA, conducted by professional bilingual translators, a panel of experts, and a pilot study, and II) validation in a sample of 42 acquired brain injury patients (ABI) and 42 healthy participants (HC). WCPA primary outcomes showed expected convergent/discriminant validity patterns with socio-demographical and clinical variables and cognitive processes identifying those WCPA outcomes that best predicted executive and memory deficits measured with a battery of traditional neuropsychological tests. In addition, performance on the WCPA was a significant predictor of everyday functioning over variables such as socio-demographics or global cognition when measured with traditional tests. External validity was established by the WCPA's ability to identify everyday cognitive deficits in ABI patients compared to HC, even in those with subtle cognitive impairment based on neuropsychological tests. The SpanishWCPA-10 version (i.e., “Actividad de Planificación del Horario Semanal, APHS-10”) seems an appropriate and sensitive assessment tool to identify cognitive-functional impairment in ABI-patients, even those with subtle cognitive impairment. The results also highlight the relevance of this kind of test, as they indicate a better prediction of patients’ real-world functioning than traditional neuropsychological tests.